Diminishing Speckle Noise During Nonlinear Phase-only Beam Shaping - Ackermann, Lisa; Roider, Clemens; Cvecek, Kristian; Barré, Nicolas; Schmidt, Michael (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
The liquid crystal spatial light modulator (LC-SLM) is a powerful device to dynamically shape arbitrary intensity distributions and finds application in research and industry. While wave front shaping is highly efficient and thus favorable, the shaped intensity profile suffers from speckle noise and, moreover, LC-SLMs are technically limited to the visible, near-infrared and mid-infrared spectral ranges. We make use of nonlinear optics to enlarge the spectral range by shaping the light field at the fundamental but achieving the desired outcome at the second harmonic [1]. Moreover, we diminish speckle noise by temporal averaging to achieve results of high uniformity and quality. To this end, usually several different patterns are displayed sequentially on the SLM what results in poor efficiency due to the low frame rate. We overcome this problem by using a single phase mask while the beam is scanned over the SLM with a galvanometer scanner and subsequently de-scanned [2].
CRIS-Team Scopus Importer:2024-12-16